2016
DOI: 10.1111/ceo.12821
|View full text |Cite
|
Sign up to set email alerts
|

Corneal diameter and associated parameters in Chinese children: the Shandong Children Eye Study

Abstract: In 4 to 18-year-old children, larger corneal diameter was associated most strongly with flatter corneal curvature, followed by longer axial length and male gender. Corneal diameter was independent of age beyond an age of 4 years. Abnormally large and abnormally small corneas may be defined as being ≥12.76 and ≤11.24 mm in diameter, respectively. Corneal diameter was not correlated with time spent indoors/outdoors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…In this study, parameters including horizontal corneal curvature, vertical corneal curvature, and height in both 4-and 5-year-old children and weight in 5-year-old children were significantly different from 2013 to 2019; however, few significant differences were observed in paired comparisons. Jiang et al [19] found that flatter horizontal corneal curvature was significantly associated with larger corneal diameter in 4-18-year-old children, which was significantly associated with taller body height but not correlated with time outdoors. Furthermore, an abnormally large cornea (2.6%) and an abnormally small cornea (2.4%) [19] were not classified or interpreted in this study but may influence the mean value of corneal curvature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, parameters including horizontal corneal curvature, vertical corneal curvature, and height in both 4-and 5-year-old children and weight in 5-year-old children were significantly different from 2013 to 2019; however, few significant differences were observed in paired comparisons. Jiang et al [19] found that flatter horizontal corneal curvature was significantly associated with larger corneal diameter in 4-18-year-old children, which was significantly associated with taller body height but not correlated with time outdoors. Furthermore, an abnormally large cornea (2.6%) and an abnormally small cornea (2.4%) [19] were not classified or interpreted in this study but may influence the mean value of corneal curvature.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al [19] found that flatter horizontal corneal curvature was significantly associated with larger corneal diameter in 4-18-year-old children, which was significantly associated with taller body height but not correlated with time outdoors. Furthermore, an abnormally large cornea (2.6%) and an abnormally small cornea (2.4%) [19] were not classified or interpreted in this study but may influence the mean value of corneal curvature. In addition, corneal curvature was also influenced by birth weight and gestational age [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The corneal horizontal diameter ( Y ), which is relatively constant in the eyes, was also measured. The reported mean corneal diameter among Chinese people is 12 mm [4]; the lower scleral show ( X ) was adjusted accordingly (Figure 1). Success was determined when the patient could wear an average-sized prosthesis without regrafting.…”
Section: Methodsmentioning
confidence: 99%
“…Using objective measurement techniques, the HVID in adults is on average 11.8 ± 0.5 mm, ranging between 10 and 14 mm [278]. It is adult size by age 4 [279] and slightly decreases with age (by 0.2 mm between aged 10 and 80 years) [280]. Corneal diameters have also been reported to vary with sex, ethnicity and culture.…”
Section: Unknownmentioning
confidence: 99%